Mass Treatment does not reduce the prevalency of parasites in Guarani indigenous schoolchildren in Brazil (Research, Society and Development, 2021)
The high frequency of intestinal parasites is favored by environmental and socio-cultural conditions of indigenous populations, and is still a neglected public health problem. Mass administration of broad-spectrum drugs aims to reduce the prevalence and intensity of the infections. The prevalence of intestinal parasites in school-children in an indigenous Guarani village in southern Brazil, was evaluated before and after the mass treatment of the population with albendazole. In the first phase of collection of stool samples, 81.4% of them were positive for enteroparasites and in the second phase, after two doses of antiparasitic medication, 87.5% were positive. Although the prevalence of infections by some helminths has reduced after treatment, many parasites remained frequent in the studied population, showing a change in the epidemiological profile in the distribution of these diseases in the population. The prevalence of intestinal parasites in indigenous schoolchildren proved to be high even after mass treatment with albendazole.